MANAJEMEN KEPALA SEKOLAH DALAM PENINGKATAN MUTU LULUSAN - Syafaruddin Syafaruddin; Muhammad Rifa’i; Demu Wira Brutu (Universitas Muria Kudus, 2022)
The purpose of this study is to analyze the management of school principals in improving the quality of graduates at MTs Pesantren Dairi.The research method used is descriptive qualitative method. Data were collected using interviews, observation, and document studies. The data analysis technique was carried out through data reduction, data presentation and drawing conclusions.The results of the study found that: 1) Planning for improving the quality of madrasas at MTs Pesantren Dairi was carried out by the head of the madrasa through deliberation by involving other madrasa components with the aim of building commitment and responsibility so as to produce performance for leaders, teachers and education staff in terms of achievement and quality of graduates. 2) Organizing resources in improving the quality of graduates at MTs Pesantren Dairi, carried out by dividing the duties of staff, leaders, teachers and education personnel to carry out their respective main tasks and functions so that individual, unit/field and madrasa performance is achieved as expected. 3) The implementation of the graduate quality improvement program runs according to procedures that refer to the goals and graduate standards set by the madrasa management and is realized through three main programs that serve as work guidelines, namely strengthening tahfiz juz 30, developing superior classes, and strengthening student worship. 4) Supervision of improving the quality of graduates at MTs Pesantren Dairi shows that supervision is carried out through supervision, monitoring and evaluation by involving elements of the leadership and staff of the madrasa leadership in this pesantren to ensure the achievement of goals effectively and efficiently.